The Occurrence and Distribution Pattern of Antibiotic Resistance Genes and Bacterial Community in the Ili River - Yang, Xiaobo; Yan, Li; Yang, Yutong; Zhou, Hongrui; Cao, Yang; Wang, Shang; Xue, Bin; Li, Chenyu; Zhao, Chen; Zhang, Xi; Shen, Zhiqiang; Wang, Jingfeng; et al. (Frontiers in Environmental Science, 2022)
The emergence of antibiotic resistance genes (ARGs) is a great risk to the ecosystem and human health; however, there are rare systematic studies about the characterization and source identification of ARGs in continental rivers. This study examined the occurrence of bacterial communities and ARGs in the water and soil of the Ili River using bacterial testing and metagenomic sequencing. Total dissolved solids (TDSs) and total bacterial count significantly increased from upstream to downstream sites. Enterococcus showed the highest abundance in Cockdara. Metagenomic sequencing revealed that the bacterial communities of surface water were different from those of nearshore soils. Among the top 10 ARGs, fluoroquinolone and aminoglycoside resistance genes exhibited dominant relative abundance, but only the multidrug resistance gene adeF was common in all water and soil samples. Proteobacteria carried almost 61% of ARGs, suggesting that these could be the main antibiotic-resistant bacteria (ARB) in the Ili River. Proteobacteria and ARB were mainly distributed in Yining city and Cockdara. Furthermore, the distribution pattern among the five sampling sites indicated that human activity and animal husbandry greatly contributed to the ARB and ARG contamination. This study first investigated the occurrence and distribution pattern of ARGs in the Ili River, demonstrating a clear correlation between bacteria and ARGs, and ARGs and mobile genetic elements (MGEs).